Production of thermoplastic composites from carbon fibers treated by dielectric barrier discharge - Santos, A. L. [UNESP]; Botelho, E. C. [UNESP]; Kostov, K. G. [UNESP]; Toth, A.; Silva, L. L.G. (My University, 2012)
This study deals with the production and characterization of carbon-reinforced polypropylene (CF/PP) composites from carbon fibers (CFs) treated by an atmospheric pressure dielectric barrier discharge (DBD). Following the treatment the CFs were characterized by Raman spectroscopy, which demonstrated that there were no major changes in the fiber crystalline structure after the treatment. X-ray photoelectron spectroscopy (XPS) analysis revealed an incorporation of oxygen containing polar groups on the fiber surface. Atomic force microscopy (AFM) indicated that the plasma species attacked the CF surface and changed its roughness. Interlaminar shear strength test (short-beam) and subsequent observation of the composites cross-section by scanning electron microscopy (SEM) demonstrated a greater resistance to shear of the composites made with CFs treated by DBD.
Keywords: Atmospheric plasma; Carbon fibers; Composites; DBD